Factors affecting learner autonomy in the context of English language learning - Al-Khasawneh, Fadi; Huwari, Ibrahim; Alqaryouti, Marwan; Alruzzi, Kamal; Rababah, Luqman (Jurnal Cakrawala Pendidikan, 2024)
Several studies emphasized the importance of learning autonomy as a crucial component of persistent learning. Those studies revealed that autonomous learners are more likely to succeed in comparison to passive learners. The main purpose of this study is to investigate the factors affecting learning autonomy and to examine the differences between the reported factors and academic level. The researchers developed a questionnaire after extensive research on the questionnaires used in previous studies. The data have been collected from (232) undergraduate students, who were randomly selected from the Department of English Language at King Khalid University. The results showed that learning autonomy is influenced by five internal factors (i.e., psychological aspects, learning strategies, cognitive abilities, metacognitive abilities, and critical thinking), and three external factors (i.e., the role of the teacher, the task, and the environment). The results also showed that most of the internal and external factors have no statistically significant differences attributed to academic level. The results of this study recommended that educators modify their pedagogical approaches to provide students with more choices, problem-solving, and independent learning possibilities.